Implementasi Program Pembinaan Kepribadian dan Kemandirian Narapidana Lanjut Usia di Lembaga Pemasyarakatan (Universitas Islam Balitar, Blitar, 2022)
Elderly inmates have different needs from other inmates. This study aims to analyze the implementation of coaching for the elderly in correctional institutions (prisons). Through normative legal research methods, research is produced that there are still prisons that do not provide coaching following applicable laws and regulations. Many of the obstacles faced by prisons are due to the age of the elderly and the incomplete facilities and infrastructure owned by prisons to support coaching activities for elderly prisoners.